Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd006583.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic entry techniques

Abstract: An open-entry technique is associated with a significant reduction in failed entry when compared to a closed-entry technique, with no difference in the incidence of visceral or vascular injury.Significant benefits were noted with the use of a direct-entry technique when compared to the Veress Needle. The use of the Veress Needle was associated with an increased incidence of failed entry, extraperitoneal insufflation and omental injury; direct-trocar entry is therefore a safer closed-entry technique.The low rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 36 publications
1
32
0
3
Order By: Relevance
“…The laparoscopic entry phase is the biggest challenge because of the displacement of the umbilicus till the pubis and the thickness of the subcutaneous fat tissue [8]. However, the frequency of vascular or visceral injury does not differ according to the entry technique used, as reported in the 2012 Cochrane review; however, this review did not consider the effect of BMI on laparoscopic entry [18]. Entry technique guidelines published in 2008 suggest the use of a Palmer's point or open technique in morbidly obese patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…The laparoscopic entry phase is the biggest challenge because of the displacement of the umbilicus till the pubis and the thickness of the subcutaneous fat tissue [8]. However, the frequency of vascular or visceral injury does not differ according to the entry technique used, as reported in the 2012 Cochrane review; however, this review did not consider the effect of BMI on laparoscopic entry [18]. Entry technique guidelines published in 2008 suggest the use of a Palmer's point or open technique in morbidly obese patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…The primary trocar is placed without prior insufflation. This technique avoids the risks associated with Veress needle but it may increase the risk of major vessel injury [8, 9]. The main problem encountered during abdominoplasty patients seems to be perforation of fibrotic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Ahmad et al 3 identified 13 different laparoscopic-entry techniques from 28 randomized controlled studies. Indeed numbers of entry techniques are multiplying even faster in consideration of the state-of-the-art updates, which are consistently retooling operating theaters, and surgical technique modifications, but abdominal entry is always hazardous when obese patients are in the surgical room.…”
Section: Discussionmentioning
confidence: 99%
“…Of the techniques currently being used, none has been identified as being safe enough to prevent complications associated with laparoscopic entry. 3 …”
Section: Introductionmentioning
confidence: 99%